Tragic Knowledge Yeats’S Autobiography and Hermeneutics - O’Hara, Daniel T. (Columbia University Press, 1981)
Presents the outlines of a hermeneutic theory of how irony is represented in autobiographical texts, and the example of practical criticism with Yeats autobiography